Perjanjian Elektronik Pada Pinjaman Online - Nyoman Andhi Priyambawa; I Nyoman Putu Budiartha; A.A. Sagung Laksmi Dewi (Fakultas Hukum, Universitas Warmadewa, 2022)
In cyberspace, you can find technology-based financial services called online lending. All statements and approvals are made only by the debtor by pressing the smartphone screen or clicking through the computer. The purpose of this research is to find out the legal arrangements for online loan credit agreements electronically and the legal consequences if there is a default on online loans. The type of research is normative legal research with a statutory and conceptual approach. Legal materials consist of primary, secondary and tertiary legal materials, the collection of which is by literature study. legal materials were analyzed deductively with descriptive analysis and legal interpretation. The results of the study show that the implementation of online credit lending agreements is regulated in the Financial Services Authority Regulation Number 77/Pojk.01/2016 concerning Information Technology-Based Borrowing-Lending Services. Regulate the contents that must be included in the online credit loan agreement, both online credit agreements made between the provider and the lender or between the creditor and the credit recipient. The settlement of bad loans is regulated in the Code of Conduct for Responsible Information Technology-Based Lending and Borrowing Services issued by the Indonesian FinTech Association.